1993
DOI: 10.1111/j.1540-8159.1993.tb01816.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient Acceptance of the Implantable Cardioverter Defibrillator in Ventricular Tachyarrhythmias

Abstract: Besides surgical problems, recipients of implantable cardioverter defibrillators (ICDs) are faced with psychological and social adjustments. Successful ICD therapy is influenced by the patients' perceived concerns regarding device, discharge, changes in life style, and complications. In order to assess patients' acceptance of the ICD, the psychological profile of 57 consecutive patients was evaluated using a specifically designed questionnaire and the State Trait Anxiety Inventory (STAI). The results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
9

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(77 citation statements)
references
References 19 publications
0
68
0
9
Order By: Relevance
“…With the advent and then dominance of primary prevention indications, avoidable shocks assumed a relatively larger proportion of total therapy [78][79][80][81][82][83]. Gradually, publications have increased awareness of the frequency and the diverse range of adverse outcomes associated with avoidable ICD therapy, and have demonstrated that avoidable ICD shocks can be reduced by evidence-based programming of the detection rate, detection duration, antitachycardia pacing (ATP), algorithms that discriminate supraventricular tachycardia (SVT) from VT, and specific programming to minimize the sensing of noise [81][82][83][84][85][86][87][88][89][90][91][92].…”
Section: Tachycardia Detection Programmingmentioning
confidence: 99%
“…With the advent and then dominance of primary prevention indications, avoidable shocks assumed a relatively larger proportion of total therapy [78][79][80][81][82][83]. Gradually, publications have increased awareness of the frequency and the diverse range of adverse outcomes associated with avoidable ICD therapy, and have demonstrated that avoidable ICD shocks can be reduced by evidence-based programming of the detection rate, detection duration, antitachycardia pacing (ATP), algorithms that discriminate supraventricular tachycardia (SVT) from VT, and specific programming to minimize the sensing of noise [81][82][83][84][85][86][87][88][89][90][91][92].…”
Section: Tachycardia Detection Programmingmentioning
confidence: 99%
“…Uygunsuz şok esnasında hastalar bilinçli olduklarından genellikle kötü tolere edilir. Ağrı, özellikle anksiyeteye neden olan psikolojik bozukluklar, ventriküler aritmi başlatabilme ve pil ömründe azalma olumsuz özellikleri arasında sayılabilir (5,6) . Uygunsuz ICD şoklamasının en yaygın nedenleri supraventriküler taşikar-disi (sinüs taşikardisi, atriyal fi brilasyon, atriyal fl atter) ve artefaktların aşırı algılanmasıdır.…”
Section: Discussionunclassified
“…[34] już w 1993 roku wykazali w grupie 57 pacjentów z ICD, że poziom lęku oceniany za pomocą State Trait Anxiety Inventory (STAI) był istotnie wyższy w grupie chorych, którzy doświadczyli więcej niż 5 interwencji wysokoenergetycznych. Z kolein w badaniu Johansen i wsp.…”
Section: Badanie Cidsunclassified
“…Pacjenci poniżej 50. roku życia w porównaniu ze starszymi chorymi wykazują wyższy poziom lęku [34], gorzej oceniają swoją QoL oraz podobnie jak chorzy, którzy doświadczyli interwencji wysokoenergetycznych ICD wyrażają więcej obaw takich jak strach przed wysiłkiem fizycznym, co może prowadzić do ograniczania aktywności życiowej w obawie przed sprowokowaniem kolejnej interwencji ICD [51].…”
Section: Wpływ Icd Na Qol Młodych Pacjentówunclassified